The suppression of TdMRP3 genes reduces the phytic acid and increases the nutrient accumulation in durum wheat grain - Frittelli, Arianna; Botticella, Ermelinda; Palombieri, Samuela; Masci, Stefania; Celletti, Silvia; Fontanella, Maria Chiara; Astolfi, Stefania; De Vita, Pasquale; Volpato, Mirko; Sestili, Francesco (Frontiers in Plant Science, 2023)
Micronutrient malnutrition affects more than half of the world population. Reduced bioavailability of microelements in the raw materials is considered one of the main causes of mineral deficiency in populations whose diet is largely based on the consumption of staple crops. In this context, the production of low phytic acid (lpa) cereals is a main goal of the breeding programs, as phytic acid (PA) binds essential mineral cations such as iron (Fe), zinc (Zn), manganese (Mn), potassium (K), calcium (Ca) and magnesium (Mg) precipitating in the form of phytate salts poorly digested by monogastric animals, including humans, due to the lack of phytases in the digestive tract. Since PA limits the bioavailability of microelements, it is widely recognized as an anti-nutritional compound. A Targeting Induced Local Lesions IN Genomes (TILLING) approach has been undertaken to silence the genes encoding the TdABCC13 proteins, known as Multidrug-Resistance associated Proteins 3 (TdMRP3), transporters involved in the accumulation of PA inside the vacuole in durum wheat. The TdMRP3 complete null genotypes showed a significant reduction in the content of PA and were able to accumulate a higher amount of essential micronutrients (Fe, Zn, Mn) compared to the control. The number of spikelets and seeds per spike, traits associated with the agronomic performances, were reduced compared to the control, but the negative effect was in part balanced by the increased grain weight. The TdMRP3 mutant lines showed morphological differences in the root apparatus such as a significant decrease in the number of root tips, root length, volume and surface area and an increase in root average diameter compared to the control plants. These materials represent a promising basis for obtaining new commercial durum wheats with higher nutritional value.